Use of Learning Strategies in the University. A Case Study - Mitchell Alberto Alarcón Díaz (Propósitos y Representaciones, 2019)
The objective of this study was the characterization of the learning strategies of higher education students of a university in Lima. To achieve this purpose, the focus is qualitative, which allows us to interpret the same practice of the students. The methodology of this research, included direct observation and in-depth interviewing, and was aimed at understanding the reasons for practice in certain strategies. The conclusion of the research is that the metacognitive strategies, the processing of information and the control of the context become the fundamental principles at the moment of learning by students.